IMPLEMENTATION OF SOCIAL EMOTIONAL LEARNING THROUGH THE GP (GALON PERUNDUNGAN) AND AKU PEKA (PEDULI, EMPATI, KASIH SAYANG) PROGRAM AT SENDANGMULYO 02 STATE PRIMARY SCHOOL - Azizah; Sumarno; Yenny Rachmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Bullying is something you need to be careful of because it not only damages you physically but also mentally. Even more dangerous, victims of bullying can commit suicide because they do not have the resilience to face this behavior. Bullying can occur due to environmental factors, both physical internal environment and cultural and technological aspects. The ease with which a person can access the internet and the development of online game applications today is one of the causes of a person's moral degradation. Bullying can occur anytime and anywhere, including in the world of education. Schools are an environment where bullying against children develops. The efforts made by SDN Sendangmulyo 02 to prevent bullying in schools are by implementing social emotional learning for students which is framed in a special program called "GP Program (Galon Shelter) and Aku PEKA (Care, Empathy and Compassion)". This research aims to analyze the implementation of social emotional learning through the "GP and Aku PEKA" program at SD Negeri Sendangmulyo 02 and its impact in preventing bullying. The method used in this research process is observation, interviews and documentation techniques with research results in the form of descriptive analysis. The results of this research show that the "GP and Aku PEKA" program at SDN Sendangmulyo 02 has been implemented well and has succeeded in reducing bullying in schools. This program has even been able to provide an increase in school safety climate indicators, which initially decreased by 0.09% in 2023, but now in 2024 it will increase to 1.31%. Suggestions that can be given for the sustainability of this program are that there needs to be active cooperation and collaboration between teachers so that this positive program can continue consistently in creating a safe school climate for students.